Potentiostatic and galvanostatic electrodeposition of manganese oxide for supercapacitor application: a comparison study - Ali, Gomaa A. M.; M. Yusoff, Mashitah; Yun, Hau Ng; Lim, Hong Ngee; Kwok, Feng Chong (Elsevier, 2015)
The structural and electrochemical properties of manganese oxide (MnO2) electrodeposited by potentiostatic and galvanostatic conditions are studied. X‒ray diffraction analyses confirm identical MnO2 phase (ramsdellite) are deposited under potentiostatic and galvanostatic conditions. Under comparable current density during electrodeposition, MnO2 deposited by galvanostatic condition shows smaller crystallite size, less compact layered structure, higher surface area and wider band gap, in comparison to the potentiostatic deposition. The MnO2 morphology difference under different electrodeposition conditions contributes to different capacitive behaviors. The lower compactness of MnO2 deposited galvanostatically renders facile ions diffusion, leading to higher specific capacitance with low equivalent series resistance. The findings suggest galvanostatic electrodeposition is suitable to produce MnO2 nanostructure for supercapacitor application.